The Influence of Job Satisfaction on Loyalty of Tourism Buses’ Drivers and Their Assistants in Malang through Organizational Commitment - Luthfi Jauharotun Nisa'; Lohana Juariyah (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Malang, 2018)
A person’s loyalty is a form of loyalty to an object, both people and tasks. But in fact in the current era, loyalty is a difficult thing to find. Human resources who born in 1983-1997 or called Y generation have lower loyalty than X generation (1963-1982). So that studying loyalty of tourism buses’ drivers and their assistants is an interesting thing in order to know what cause the loyalty of drivers and their assistants. The purpose of this study are (1) to find out the description of job satisfaction, organizational commitmen and driver and kernet loyalty, (2) to find out whether there is a significant positive influence on job satisfaction on the driver's and kernet's organizational commitment, (3) to find out whether there is a positive influence significant organizational commitment to driver and kernet loyalty, (4) to determine whether there is a significant positive influence on job satisfaction on driver and kernet loyalty, (5) and to find out whether there is a significant positive effect on job satisfaction on driver loyalty and kernet through organizational commitment. This research is quantitative and using path analysis to determine the relationship between variables. The sampling method uses purposive sampling in the form of judment sampling. Population in this research is 125 driver and kernet in Malang with sample 105 driver and kernet. Data collection methods use a closed questionnaire. The research results show that: (1) Job satisfaction has a positive and significant effect on the driver's and kernet's organizational commitment; (2) Organizational commitment has a positive and significant influence on driver and kernet loyalty; (3) Job satisfaction has a positive and significant impact on driver and kernet loyalty; (4) Job satisfaction affects the loyalty of driver and kernet through organizational commitment.